CHALLENGES JORDANIAN MILITARY INTERPRETERS FACE IN INTERPRETING MILITARY TOPICS AND THE TECHNIQUES TO OVERCOME THEM - Hythem Wanas Al-Sad; Kamariah Yunus (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The demand for military translation and interpretation has increased among nations due to new military technologies, international military cooperation, and the current geopolitical situation. However, military language comprises a blend of new terminology, acronyms, and abbreviations, slang terms, and jargon. Also, the growing demand for military interpretation may also potentially challenge interpreters in rendering the correct interpretation into Arabic. Thus, the aim of this study is to explore and understand the difficulties facing interpreters alongside exploring the appropriate techniques and methods to overcome some of these difficulties and challenges like acronyms, abbreviations, and slang military terminologies. The research was conducted through a qualitative approach using the interviews method with 50 participants; enough to reach saturation level of data collection. Then, thematic analysis was employed to identify and analyze the data. The current study finds out that the most significant difficulties military interpreters face are mainly linguistic, cultural difficulties, military environment, and gender-related challenges. However, the most significant linguistic challenges in military interpretation are acronyms, abbreviations, and slang terms. Moreover, military interpreters encounter frequent challenges in interpreting new military lexis and military terminologies. The current study suggests the most available techniques military interpreters use to overcome this challenge. The full expansion of English acronyms is the most common method military interpreters use while Coining Arabic acronyms is lesser used. However, borrowing the English acronyms technique is infrequently used to interpret English military acronyms. Recommendations made by this study will hopefully increase the research base for the field of military interpretation and, therefore, enhance the ability to perform better military interpretation in the future.